Phylogenetic evidence and morphological diagnosis for a new species of Parasesarma De Man, 1895 (Decapoda, Brachyura, Sesarmidae) from Sulawesi, Indonesia - Shahdadi, Adnan; Schubart, Christoph D.; Mendoza, Jose Christopher E. (Zootaxa, 2023)
A new species of Parasesarma, P. rahayuae n. sp., is described from Sulawesi, Indonesia. Genetically, the new species is distinct from all other known species of Parasesarma and has a close phylogenetic relationship with P. anambas Yeo, Rahayu & Ng, 2004 and P. gemmatum Li, Shih & Ng, 2019. Morphologically, the new species most closely resembles P. anambas and P. gemmatum, but can be distinguished from these two species by the shape of the dactylar tubercles of the male chela and of the male first gonopod. This is the fourth species of Parasesarma recorded from Sulawesi, and with its description, the number of species assigned to the genus Parasesarma is 58.